Self-adjuvanted mRNA vaccination in advanced prostate cancer patients: a first-in-man phase I/IIa study. Issue 1 (16th June 2015) - Kübler, Hubert; Scheel, Birgit; Gnad-Vogt, Ulrike; Miller, Kurt; Schultze-Seemann, Wolfgang; vom Dorp, Frank; Parmiani, Giorgio; Hampel, Christian; Wedel, Steffen; Trojan, Lutz; Jocham, Dieter; Maurer, Tobias; et al.
Abstract : Background: CV9103 is a prostate-cancer vaccine containing self-adjuvanted mRNA (RNActive®) encoding the antigens PSA, PSCA, PSMA, and STEAP1. This phase I/IIa study evaluated safety and immunogenicity of CV9103 in patients with advanced castration-resistant prostate-cancer. Methods: 44 Patients received up to 5 intra-dermal vaccinations. Three dose levels of total mRNA were tested in Phase I in cohorts of 3–6 patients to determine a recommended dose. In phase II, 32 additional patients were treated at the recommended dose. The primary endpoint was safety and tolerability, the secondary endpoint was induction of antigen specific immune responses monitored at baseline and at weeks 5, 9 and 17. Results: The most frequent adverse events were grade 1/2 injection site erythema, injection site reactions, fatigue, pyrexia, chills and influenza-like illness. Possibly treatment related urinary retention occurred in 3 patients. The recommended dose was 1280 μg. A total of 26/33 evaluable patients treated at 1280 μg developed an immune response, directed against multiple antigens in 15 out of 33 patients. One patient showed a confirmed PSA response. In the subgroup of 36 metastatic patients, the Kaplan-Meier estimate of median overall survival was 31.4 months [95 % CI: 21.2; n.a]. Conclusions: The self-adjuvanted RNActive® vaccine CV9103 was well tolerated and immunogenic. The technology is a versatile, fast and cost-effective platform allowing for creation of vaccines. The follow-up vaccine CV9104 including the additional antigens prostatic acid phosphatase (PAP) and Muc1 is currently being tested in a randomized phase IIb trial to assess the clinical benefit induced by this new vaccination approach. Trial registration: EU Clinical Trials Register: EudraCT number 2008-003967-37, registered 27 Jan 2009.